Effect of Various Solvent on the Synthesis of NiO Nanopowders by Simple Sol-Gel Methods and Its Characterization - Sherly Kasuma Warda Ningsih (Indonesian Journal of Chemistry, 2015)
Synthesis of nickel oxide (NiO) with various solvents by simple sol-gel process has been done. NiO nanopowders were obtained by using nickel nitrate hexahydrate and sodium hydroxide 5 M were used as precursor and agent precipitator, respectively. The addition of various solvents that used in this research were aquadest, methanol and isopropanol. The powders were formed by drying in the temperature of 100-110 °C for 1 h and after heating at ±450 °C for 1 h. The products were obtained black powders. The products were characterized by Energy Dispersive X-Ray Fluorescence (ED-XRF), X-Ray Diffraction (XRD) and Scanning Electron Microscopy (SEM). The ED-XRF pattern show that composition of NiO produced was 96.9%. The XRD patterns showed NiO forms were in monoclinic structure with aquadest solvent and cubic structure with methanol and isopropanol used. Crystal sizes of NiO particles produced with aquadest, methanol, isopropanol were obtained in the range 37.05; 72.16; 66.04 nm respectively. SEM micrograph clearly showed that powder had a spherical shape with uniform distribution size is 0.1-1.0 µm approximately.